How to locate and acquire Japanese scientific and technical information : (NTIS, 1993)
Contents: This volume presents the proceedings of a conference entitled "How to locate and acquire Japanese scientific and technical information" held on March 18-19, 1993, in San Francisco. Sponsored by the Japan Information Center of Science and Technology (JICST) and the U.S. National Technical Information Service (NTIS), the conference presents an important step taken to fulfill the 1988 U.S.-Japan Agreement on Cooperation in Science and Technology.